International Organizations Programmes Implementation in Nigeria: Problems and Ways Forward - Ogunode, Niyi Jacob; Ukozor , Conrad Ugochukwu; Agbo, Richmond Chijioke (International Journal of Global Sustainable Research, 2024)
The paper explores the obstacles to the implementation of international organizations' programs and projects in Nigeria, using social role theory and secondary data. The study found that inadequate funding, poor financial bilateral agreements, lack of data, insecurity, corruption, bureaucratic problems, and political interferences hinder the success of these organizations. The paper recommends increased funding for international organizations, adherence to financial organizations' paths, and the creation of an ICT system to curb corruption. It also suggests timely communication with international organizations to ensure their programs are implemented as planned. The findings underscore the need for effective governance and support for international organizations in Nigeria.